Caracterização banda-larga do canal rádio utilizando a teoria uniforme da difração - Kleber Lopes Borges (2003)
This work consists in the utilization of asymptotic techniques for the broad band radio channel characterization. Techniques for calculation of the electromagnetic field scattering in the frequency and time domains are presented. For the achievement of this scattered field, it is used a combination of ray-tracing, Geometric Optics (GO) and Uniform Theory of Diffraction (UTD). In the frequency domain, three heuristical diffraction coefficients for lossy wedges have been studied, from which a new one was proposed that presents minors errors for diffracted field in shadow regions. Comparing it with the Maliuzhinets solution, the mean errors for the diffracted field had been 1,24 and 1,51 dB for TM and TE polarizations, respectively. These errors are less than the errors presented by otherscoefficients, being acceptable in problems involving channel radio characterization in urban environments. The problem of the double diffraction in consecutive edges was also considered, in which higher order diffraction coefficients ( slope diffraction ) were used for the field calculation. The results obtained from the UTD have been comparedwith the reference ones from integral equations solved by the Method of Moments. To consider the losses in the Method of Moments, impedance boundary conditions of Leontovich type were used (MoM+IBC).For the time analysis, the Time Domain Uniform Theory of Diffraction (TDUTD) was used for the scattered field evaluation. Such analysis is important because the wideband propagation study in time domain has physical meaning. Other reason for its utilization is that using a time domain formulation does not present problems related with the application of IFFT, as aliasing, that is minimized taking a wider time window. This solution requires more frequencies to be analyzed. The TD-UTD expressions for the direct, reflected and difracted rays were obtained from the application of the Analytic Time Transform (ATT) in the respective expressions of the frequency domain. Due to the difficulty of evaluating a TD-UTD formulation for lossy obstacles, the TDUTDpresented in this work considers only electric and magnetic perfect conductors. The numerical results have been compared with those yield by the application of a Inverse Fourier Transform into the results of the UTD and the Method of Moments in frequency domain. In the channel radio characterization, the consideration of the ground as a perfect magnetic conductor for the TD-UTD is the one that supplies thebest approach for a vertical polarization in a lossy environment, and the result is better when the receiving antenna is in the line of sight of the transmitter.